Silicon-carbon composite material, method for manufacturing same, and negative electrode active material and lithium secondary battery comprising same
By using silicon-carbon composite materials with suitable oxygen content in lithium secondary batteries, combined with etching and chemical thermal decomposition deposition technology, the silicon-carbon composite materials with core-shell structures are solved, and the volume expansion and contraction problems in lithium secondary batteries are solved. , improves battery performance and capacity retention.
Patent Information
- Application Number
- CN202380032717.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-17
- Filing Date
- 2023-02-17
- Publication Date
- 2024-12-17
AI Technical Summary
The existing silicon-based negative electrode active materials have problems with volume expansion and contraction in lithium secondary batteries, resulting in a decrease in capacity retention and cycling characteristics, and it is difficult for the prior art to effectively suppress these problems.
Using a silicon-carbon composite material with an oxygen content of 0.01 to 0.45, the silicon-based raw material was etched and filtered by etching solution, and then a carbon layer was applied inside the silicon composite material using a chemical thermal decomposition deposition method to form a core-shell structure. silicon-carbon composite materials to improve conductivity and mechanical properties.
The discharge capacity, initial efficiency and capacity retention rate of lithium secondary batteries are significantly improved, the electrode expansion rate is reduced, and the method is suitable for large-scale production.
Smart Images

Figure CN119156347A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon-carbon composite material, a method for preparing the silicon-carbon composite material, and a negative electrode active material and a lithium secondary battery containing the silicon-carbon composite material. Background Art
[0002] In recent years, as electronic devices have become smaller, lighter, thinner and more portable with the development of the information industry and the communication industry, there is an increasing demand for high energy density of batteries used as power sources for these electronic devices. Lithium secondary batteries are the batteries that best meet this demand, and small batteries using lithium secondary batteries and their applications in large electronic devices such as automobiles and energy storage systems are being actively studied.
[0003] Carbon materials are widely used as negative electrode active materials for such lithium secondary batteries. In order to further increase the capacity of the battery, silicon-based negative electrode active materials are being studied. Since the theoretical capacity of silicon (4199 mAh / g) is 10 times or more higher than the theoretical capacity of graphite (372 mAh / g), it is expected that the battery capacity can be significantly increased.
[0004] For example, when lithium is intercalated into silicon, the reaction equation is as follows:
[0005] [Reaction 1]
[0006] 22Li+5Si=Li 22 Si5
[0007] In the silicon-based negative electrode active material according to the above reaction formula, an alloy containing up to 4.4 lithium atoms / silicon atom with high capacity is formed. However, in most silicon-based negative electrode active materials, the insertion of lithium causes a volume expansion of up to 300%, which damages the negative electrode, making it difficult to exhibit high cycle characteristics.
[0008] In addition, this volume change may cause cracks to appear on the surface of the negative electrode active material, and ionic materials may be formed inside the negative electrode active material, causing the negative electrode active material to be electrically separated from the current collector. This electrical separation phenomenon may significantly reduce the capacity retention rate of the battery.
[0009] In order to solve this problem, Japanese Patent No. 4393610 discloses a negative electrode active material in which silicon and carbon are mechanically processed to form a composite material, and a carbon layer is coated on the surface of silicon particles using a chemical vapor deposition (CVD) method. In addition, Japanese Laid-Open Patent Publication No. 2016-502253 discloses a negative electrode active material, the negative electrode active material comprising silicon-based particles and carbon particles, wherein the carbon particles comprise fine carbon particles and coarse carbon particles having different average particle diameters.
[0010] However, although these prior art documents relate to negative electrode active materials comprising silicon and carbon, there are limitations in suppressing volume expansion and contraction during charge and discharge. Therefore, research is still needed to solve these problems.
[0011] [Prior art literature]
[0012] [Patent Document]
[0013] (Patent Document 1) Japanese Patent No. 4393610
[0014] (Patent Document 2) Japanese Laid-Open Patent Publication No. 2016-502253. Summary of the invention
[0015] Technical issues
[0016] The present invention aims to solve the above-mentioned problems of the prior art. Its purpose is to provide a silicon-carbon composite material, which comprises silicon particles and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material satisfies a specific range, so that when it is applied to a negative electrode active material, it has excellent capacity retention, and has significantly improved discharge capacity and initial efficiency.
[0017] In addition, another object of the present invention is to provide silicon-carbon composite materials having various structures with a core-shell structure.
[0018] In addition, another object of the present invention is to provide a method for preparing the silicon-carbon composite material.
[0019] In addition, another object of the present invention is to provide a negative electrode active material including the silicon-carbon composite material and a lithium secondary battery including the negative electrode active material.
[0020] Solution to the problem
[0021] In order to achieve the above-mentioned object, the present invention provides a silicon-carbon composite material, which comprises silicon particles and carbon, wherein the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material is 0.01 to 0.45.
[0022] In addition, the present invention provides a method for preparing a silicon-carbon composite material, which includes a first step of etching a silicon-based raw material powder using an etching solution containing a compound containing fluorine (F) atoms; a second step of filtering and drying the product obtained by etching to prepare a silicon composite material; and a third step of coating carbon on the interior of the silicon composite material using a chemical thermal decomposition deposition method or coating carbon on the interior of the silicon composite material and forming a carbon layer on its surface to obtain a silicon-carbon composite material.
[0023] Furthermore, the present invention provides a negative electrode active material comprising the silicon-carbon composite material.
[0024] Furthermore, the present invention provides a lithium secondary battery including the negative electrode active material.
[0025] Advantageous Effects of the Invention
[0026] According to the embodiment, since the silicon-carbon composite material comprises silicon particles and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material satisfies a specific range, when it is used as a negative electrode active material of a lithium secondary battery together with a binder and a conductive material to prepare a negative electrode active material composition, it is easy to disperse, and the mechanical properties (such as strength) are excellent, and the performance of the lithium secondary battery can be improved. In addition, when the porosity of the silicon-carbon composite material is controlled, the discharge capacity, initial efficiency and capacity retention rate of the lithium secondary battery can be further improved.
[0027] According to another embodiment, the silicon-carbon composite material has a core-shell structure, and the core contains silicon particles and carbon, and in particular, the shell includes at least one or two or more carbon layers, thereby further improving the strength of the shell layer, and enhancing the bonding (adhesion) between the silicon-carbon composite material and the binder, which can reduce the electrode expansion rate. Therefore, the discharge capacity, initial efficiency and capacity retention rate of the lithium secondary battery can be improved at the same time.
[0028] Furthermore, the preparation method according to the embodiment is advantageous in that large-scale production can be performed through a continuous process with a minimum number of steps. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The following drawings attached to this specification illustrate preferred embodiments of the present invention and are used together with the description of the present invention to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted as being limited to the embodiments depicted in the drawings.
[0030] Figure 1 is a schematic diagram illustrating a method for preparing a silicon-carbon composite material according to an embodiment.
[0031] Figure 2 A photograph with a magnification of 30,000 of the silicon composite material (B1) prepared in Example 1 analyzed by an ion beam scanning electron microscope (FIB-SEM) is shown.
[0032] Figure 3 A photograph with a magnification of 30,000 of the silicon-carbon composite material prepared in Example 1 analyzed by an ion beam scanning electron microscope (FIB-SEM) is shown.
[0033] Figure 4An ion beam transmission electron microscope (TEM-FIB) photograph of the silicon-carbon composite material prepared in Example 1 is shown.
[0034] Figure 5 The measurement results of the X-ray diffraction analysis of the silicon-carbon composite material prepared in Example 1 are shown.
[0035] Figure 6 The measurement results of the Raman spectrum of the silicon-carbon composite material prepared in Example 1 are shown.
[0036] Figure 7 The measurement results of the X-ray diffraction analysis of the silicon-carbon composite material prepared in Example 4 are shown. DETAILED DESCRIPTION
[0037] The present invention is not limited to the contents disclosed below. Instead, it can be modified in various forms as long as the gist of the present invention is not changed.
[0038] In the drawings attached to this specification, some components are exaggerated, omitted or schematically depicted, and the size of each component does not completely reflect its actual size.
[0039] In this specification, the same reference numerals denote the same elements.
[0040] The terms used in this specification are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression encompasses a plural expression.
[0041] In this specification, when one component is described as being formed on or under other components, it means that one component is directly formed on or under other components, or is indirectly formed on or under other components through another component.
[0042] In this specification, unless otherwise specified, when a component is referred to as “comprising” an element, it should be understood that the component may also include other elements.
[0043] Moreover, unless otherwise indicated, all numbers and expressions relating to quantities of ingredients, reaction conditions and the like used herein are to be understood as being modified by the term "about".
[0044] [Silicon Carbon Composite Materials]
[0045] The silicon-carbon composite material according to the embodiment includes silicon particles and carbon, wherein a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material is 0.01 to 0.45.
[0046] Since the silicon-carbon composite material according to the embodiment includes silicon particles and carbon, sufficient conductivity of the silicon-carbon composite material can be ensured, and the specific surface area can be appropriately adjusted. Therefore, when it is used as a negative electrode active material for a lithium secondary battery, the performance of the lithium secondary battery can be further improved. In addition, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material satisfies a specific range, thereby significantly improving the discharge capacity and initial efficiency while maintaining excellent capacity retention.
[0047] Specifically, according to the embodiment, most of the silicon dioxide contained in the silicon-carbon composite material can be removed by etching. In this case, the surface of the silicon particles can contain a very high fraction of silicon (Si) atoms compared to oxygen (O) atoms. In other words, the molar ratio O / Si can be significantly reduced. Due to the use of the silicon-carbon composite material as the negative electrode active material, it is preferably possible to obtain a lithium secondary battery with excellent discharge capacity, while the initial efficiency of the lithium secondary battery can be improved.
[0048] The molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the silicon-carbon composite material may be 0.01 to 0.45, preferably 0.06 to 0.45, more preferably 0.05 to 0.35, and most preferably 0.06 to 0.25.
[0049] When the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material is equal to or greater than the lower limit of the above range, the expansion and contraction caused by the charging and discharging of the lithium secondary battery can be suppressed. Therefore, when the silicon-carbon composite material is used as a negative electrode active material, the negative electrode active material can be suppressed from peeling off the negative electrode collector. In addition, if the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is equal to or less than the upper limit of the above range, sufficient discharge capacity can be ensured so that higher charge and discharge characteristics can be maintained.
[0050] Hereinafter, the structure of the silicon-carbon composite material according to the embodiment will be described in detail.
[0051] Structure of silicon-carbon composite materials
[0052] The silicon-carbon composite material according to the embodiment includes silicon particles and carbon.
[0053] Figure 1 is a schematic diagram illustrating a method for preparing a silicon-carbon composite material according to an embodiment. Figure 1 (C) and Figure 1 (D) shows a schematic diagram of a cross section of the structure of the silicon-carbon composite material according to various embodiments of the present invention. The preparation method of the silicon-carbon composite material described below is described in detail. Figure 1 (B) and a method for preparing the same.
[0054] First, refer to Figure 1 (C) and Figure 1 (D) The silicon-carbon composite material comprises silicon particles (20) and carbon (45).
[0055] The silicon-carbon composite material may include silicon particles (20), specifically silicon agglomerates in which the silicon particles (20) are bonded to each other (or connected to each other). A carbon layer (40) may be formed on the surface of the silicon particles and / or silicon agglomerates, and carbon (45) may be formed to be uniformly dispersed and / or distributed between the silicon particles (20).
[0056] In this specification, the term "bonded (or interconnected)" means a state in which silicon particles in the silicon-carbon composite material are bonded (fused) to at least another silicon particle and connected to each other, or a structure in which silicon particles are continuously connected (silicon agglomerate).
[0057] The interior of the silicon-carbon composite material can be more firmly bonded by the carbon (45) and the carbon layer (40). Therefore, the pulverization of the silicon-carbon composite material that may be caused by the volume change during the charging and discharging process of the lithium secondary battery can be minimized.
[0058] The silicon-carbon composite material is a composite material in which silicon agglomerates (in which a plurality of silicon particles (20) are bonded to each other) are uniformly distributed in a composite material having a structure in the form of a single block (e.g., a polyhedral shape, a sphere, or the like). It may be a single composite material in which carbon (45) and a carbon layer (40) containing carbon surround part or all of the surface of one or more silicon particles, or surround the surface of secondary silicon particles (silicon agglomerates) formed by the agglomeration of two or more silicon particles.
[0059] That is, in the silicon-carbon composite material, a large amount of carbon (45) is formed inside it, and a carbon layer (40) containing carbon is uniformly formed in a state of surrounding silicon particles (20); therefore, it has the advantages of ensuring high conductivity and reducing the addition of carbon-based negative electrode active materials when manufacturing a negative electrode. In addition, the specific surface area of the silicon-carbon composite material is appropriately adjusted, so that the performance of the lithium secondary battery can be further improved.
[0060] Furthermore, the silicon-carbon composite material may include pores (10).
[0061] When the silicon-carbon composite material includes pores (10), the volume expansion of the silicon particles (20) that may occur during the charging and discharging process of the lithium secondary battery can be accommodated through the pores, thereby effectively alleviating and suppressing the problems caused by the volume expansion.
[0062] Meanwhile, according to the embodiment, the silicon-carbon composite material may have a core-shell structure.
[0063] Specifically, the silicon-carbon composite material may have a core-shell structure, wherein the inner core may include silicon particles and carbon, and the outer shell may include a carbon layer.
[0064] The silicon-carbon composite material including a core-shell structure according to the embodiment may include an outer shell including a carbon layer (carbon thin film) on a surface of an inner core.
[0065] In the silicon-carbon composite material, the carbon layer forming the outer shell can be formed or laminated in various ways as long as the desired effect is not impaired. The outer shell can include up to four carbon layers, specifically one to four carbon layers, preferably one to three carbon layers, such as one or two carbon layers.
[0066] For example, according to the embodiment, there may be provided a silicon-carbon composite material having a core-shell structure in which an outer shell has a single-layer structure consisting of a first carbon layer (hereinafter referred to as “silicon-carbon composite material (1)”).
[0067] Specifically, refer again to Figure 1 (C), the silicon-carbon composite material (1) may have a core-shell structure, wherein the core may contain silicon particles (20) and carbon (45), and the shell may include a first carbon layer (40). In addition, the silicon-carbon composite material (1) may include pores (10).
[0068] Since the silicon-carbon composite material (1) includes a carbon layer having a single-layer structure on the surface of the inner core, the strength can be improved, excellent electrical conductivity can be ensured even after the electrode expands during charging and discharging, and side reactions with the electrolyte are suppressed, so that the charging and discharging capacity, initial charging and discharging efficiency and capacity retention rate of the secondary battery can be improved.
[0069] According to another embodiment, a silicon-carbon composite material having a core-shell structure may be provided, wherein the shell has a multilayer structure including at least two carbon layers, the carbon layers including a first carbon layer and a second carbon layer (hereinafter referred to as "silicon-carbon composite material (2)").
[0070] That is, the outer shell may have a multi-layer structure including at least two carbon layers including a first carbon layer and a second carbon layer.
[0071] Specifically, refer again to Figure 1 (D), the silicon-carbon composite material (2) may have a core-shell structure, wherein the core may contain silicon particles (20) and carbon (45), and the shell may include a first carbon layer (40) and a second carbon layer (50) formed on the first carbon layer (40). In addition, the silicon-carbon composite material (2) may include pores (10).
[0072] When the outer shell is composed of at least two carbon layers, even if a crack is formed on the surface of one carbon layer, the carbon layers can be kept electrically connected until the other carbon layer without the crack is completely separated.
[0073] The first carbon layer may be present on the surface of the inner core.In addition, the first carbon layer may be present on the surface of the silicon particles and / or silicon agglomerates.
[0074] In addition, the outer shell has a structure surrounding the inner core, wherein at least one carbon layer (ie, the first carbon layer) or at least two carbon layers (including the first carbon layer and the second carbon layer) used can produce the effect of a buffer layer (mitigation layer).
[0075] The buffer layer is effective as a mechanical buffer support around the core. More specifically, the buffer layer can inhibit degradation, cracking, and volume expansion of the core caused by mechanical expansion of silicon during charge and discharge.
[0076] The specific characteristics of the silicon-carbon composite materials (1) and (2) are described in more detail in the various embodiments of the silicon-carbon composite materials described below.
[0077] Physical properties of silicon-carbon composites
[0078] The average particle diameter of silicon-carbon composite material (D 50 ) can be from 2μm to 15μm.
[0079] In addition, the average particle diameter (D 50 ) is the average particle diameter (D 50 ) (i.e. the particle size or median diameter when the cumulative volume is 50%). If the average particle diameter (D 50 ) is smaller than the above range, there is a concern that the dispersibility may be deteriorated due to agglomeration of the silicon-carbon composite particles during the process of using the silicon-carbon composite to prepare a negative electrode slurry (i.e., a negative electrode active material composition). On the other hand, if the average particle diameter (D 50 ) exceeds the above range, the expansion of the silicon-carbon composite material particles caused by the charging of lithium ions becomes serious, and as charging and discharging are repeated, the bonding ability between the silicon-carbon composite material particles and the bonding ability between the particles and the collector deteriorate, so that the life characteristics may be significantly reduced. In addition, there is a concern that the activity may deteriorate due to the reduction in specific surface area.
[0080] Specifically, the average particle diameter (D 50 ) may preferably be 3 μm to 10 μm, more preferably 3 μm to 8 μm. More specifically, considering the optimization of the average particle diameter (D 50) has a significant improvement effect, and the average particle diameter of the silicon-carbon composite material particles (D 50 ) can be 3μm to 6μm.
[0081] The silicon-carbon composite material may have a core-shell structure, and the average particle diameter of the core may be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 2 μm to 6 μm.
[0082] The specific surface area of silicon-carbon composite materials (Brunauer-Emmett-Teller method; BET) can be 2 m 2 / g to 50m 2 / g, preferably 2m 2 / g to 40m 2 / g, more preferably 2m 2 / g to 20m 2 / g. If the specific surface area of the silicon-carbon composite material is less than the above range, the charge and discharge characteristics of the lithium secondary battery may deteriorate. If it exceeds the above range, it may be difficult to prepare a negative electrode active slurry suitable for application to the negative electrode collector of the lithium secondary battery, the contact area with the electrolyte increases, and the decomposition reaction of the electrolyte may be accelerated, or a side reaction of the lithium secondary battery may be caused.
[0083] In addition, the density of silicon-carbon composite materials can be 1.8 g / cm 3 Up to 2.5g / cm 3 , preferably 2.0 g / cm 3 Up to 2.5g / cm 3 , more preferably 2.0 g / cm 3 Up to 2.4g / cm 3 The density may vary depending on the coverage amount of the carbon layer, and may improve the strength of the matrix of the negative electrode active material, thereby improving the initial efficiency or cycle life characteristics. In this case, the density may refer to the true density.
[0084] When the density of the silicon-carbon composite material is equal to or greater than the lower limit of the above range, cracks in the negative electrode active material powder caused by volume expansion and contraction of the negative electrode active material powder during charging and discharging can be minimized, thereby suppressing cycle degradation. When the density is equal to or less than the upper limit of the above range, the permeability of the electrolyte is improved, which improves the initial charge and discharge capacity.
[0085] When a silicon-carbon composite material is used as a negative electrode active material in an electrode (negative electrode), the electrode expansion rate can be 55% to 150%, preferably 55% to 100%, and more preferably 60% to 80% based on the thickness of the electrode after one charge and discharge cycle.
[0086] The value of the electrode expansion rate can be converted into a percentage ratio of the thickness of the rolled negative electrode before electrode manufacturing (N1) to the thickness of the negative electrode when the cycle life is measured during the secondary battery evaluation using the secondary battery manufactured from the negative electrode and the measurement is terminated at 80% of the cycle life (N2).
[0087] [Equation A]
[0088] Electrode expansion rate (%) = thickness of negative electrode when measuring at 80% of cycle life (N2) / thickness of rolled negative electrode before electrode manufacturing (N1) × 100
[0089] In the silicon-carbon composite material, a silicon-carbon composite material (1) having a single-layer structure in which the outer shell is composed of a first carbon layer and a silicon-carbon composite material (2) having a multi-layer structure in which the outer shell includes at least two carbon layers (including a first carbon layer and a second carbon layer) may also have the same or similar properties.
[0090] Each component of the silicon-carbon composite material will be described in detail below.
[0091] Silicon particles
[0092] The silicon-carbon composite material according to the embodiment includes silicon particles.
[0093] In addition, the silicon-carbon composite material may include a silicon agglomerate in which silicon particles are bonded to each other. Specifically, the silicon-carbon composite material may include a silicon agglomerate having a three-dimensional (3D) structure in which two or more silicon particles are bonded to each other.
[0094] Since silicon particles are filled with lithium, if silicon particles are not used, the capacity of the lithium secondary battery may be reduced. The silicon particles may be crystalline or amorphous, and specifically may be amorphous or a phase similar thereto.
[0095] If the silicon particles are crystalline, a dense composite material can be obtained because the size of the crystallites is small, which improves the strength of the matrix to prevent cracks. Therefore, the initial efficiency or cycle life characteristics of the lithium secondary battery can be further improved. In addition, if the silicon particles are amorphous or a phase similar thereto, the expansion or contraction during the charging and discharging process of the lithium secondary battery is small, and the battery performance (such as capacity characteristics) can be further improved.
[0096] Although silicon particles have high initial efficiency and battery capacity, there are very complex crystal changes due to the electrochemical absorption, storage and release of lithium atoms.
[0097] Silicon particles can be evenly distributed inside the silicon-carbon composite material. In this case, excellent mechanical properties such as strength can be achieved.
[0098] In addition, the silicon-carbon composite material may have a structure in which silicon particles and carbon are uniformly dispersed.
[0099] Furthermore, preferably, the silicon particles and / or silicon agglomerates in which the silicon particles are bonded to each other in the silicon-carbon composite material are uniformly distributed inside the silicon-carbon composite material.
[0100] In addition, the silicon agglomerates as active materials can be evenly distributed inside the silicon-carbon composite material, and can contain silicon particles that are not bonded to each other. Silicon particles and / or silicon agglomerates can be evenly distributed inside the silicon-carbon composite material. In this case, excellent electrochemical properties such as charging and discharging can be achieved.
[0101] The silicon particles included in the silicon-carbon composite material according to the embodiment may be in an amorphous form, a crystalline form having a grain size of 2 nm to 10 nm, or a mixture thereof.
[0102] Specifically, when the silicon-carbon composite material is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target and calculated by the Scherrer equation based on the full width at half maximum (FWHM) of the diffraction peak of Si (220) near 2θ=47.5°, the grain size of the silicon particles can be 2nm to 10nm, preferably 2nm to 8nm, and more preferably 2nm to 5nm.
[0103] If the silicon particles include a crystalline form, and if the grain size of the silicon particles is less than 2 nm, it is not easy to prepare them, and the yield after etching may be low. In addition, if the grain size of the silicon particles exceeds the above range, the micropores cannot fully suppress the volume expansion of the silicon particles during charging and discharging, there are regions that do not contribute to discharge, and the reduction in Coulomb efficiency (which represents the ratio of charging capacity to discharging capacity) cannot be suppressed.
[0104] Based on the total weight of the silicon-carbon composite material, the content of silicon (Si) in the silicon-carbon composite material can be 38 wt % to 80 wt %, preferably 40 wt % to 80 wt %, more preferably 50 wt % to 80 wt %, even more preferably 50 wt % to 70 wt %.
[0105] If the content of silicon (Si) is less than the above range, the amount of active material for occluding and releasing lithium is small, which may reduce the charge and discharge capacity of the lithium secondary battery. On the other hand, if it exceeds the above range, the charge and discharge capacity of the lithium secondary battery may increase, and the expansion and contraction of the electrode during the charge and discharge process may increase excessively, and the negative electrode active material powder may be further powdered, which may deteriorate the cycle characteristics.
[0106] Silicon oxide compounds
[0107] According to an embodiment, the silicon-carbon composite material may further include a silicon oxide compound.
[0108] In the present invention, silicon oxide compounds are a general term for amorphous silicon compounds obtained by cooling and precipitating silicon monoxide formed by oxidation of metallic silicon, reduction of silicon dioxide, or heating a mixture of silicon dioxide and metallic silicon. x In the above formula, x may be 0.4≤x≤2, preferably 0.4≤x<1.5, and more preferably 0.4≤x<1.2.
[0109] In addition, when using low-grade silicon oxide powder (i.e. SiO x When the powder is 0.4≤x≤1.2), lithium silicate can be uniformly formed in the silicon-carbon composite material, thereby alleviating volume expansion. Therefore, the cycle characteristics of the lithium secondary battery can be improved.
[0110] In the formula SiO x In the embodiment of the present invention, if the value of x is less than the above range, the expansion and contraction may increase during the charging and discharging of the lithium secondary battery, and the life characteristics may deteriorate. In addition, if x exceeds the above range, there may be a problem that the initial efficiency of the lithium secondary battery decreases as the amount of the inactive oxide increases.
[0111] In addition, the silicon-carbon composite material may also include silicon oxide (SiO x , 0.4≤x≤2).
[0112] At the same time, based on the total weight of the silicon-carbon composite material, the content of oxygen (O) in the silicon-carbon composite material can be 0.5 wt % to 10 wt %, preferably 0.5 wt % to 8 wt %, and more preferably 0.5 wt % to 6 wt %. If the content of oxygen (O) in the silicon-carbon composite material is less than the above range, the degree of expansion during the charging process of the lithium secondary battery may increase. If the content of oxygen (O) in the silicon-carbon composite material exceeds the above range, the irreversible reaction with lithium increases, which may make the initial charge and discharge efficiency of the lithium secondary battery worse, the negative electrode active material may easily peel off from the negative electrode collector, and the charge and discharge cycle may deteriorate.
[0113] At the same time, generally, as the proportion of oxygen in the negative electrode active material containing silicon decreases, the proportion of silicon particles as active materials increases, thereby improving the discharge capacity and discharge efficiency, but there may be a problem of cracks formed in the silicon-carbon composite material due to volume expansion caused by charging and discharging of silicon particles. Therefore, the cycle characteristics of the lithium secondary battery may deteriorate. In order to solve this problem, silicon dioxide as an inert material or inert phase can be included in the silicon-carbon composite material.
[0114] Specifically, because silicon dioxide is an inert material or inert phase, it effectively mitigates the volume expansion caused by the charging and discharging of silicon particles. Silicon dioxide is a component used to form a matrix in a silicon-carbon composite material, which improves the mechanical strength of the matrix of the silicon-carbon composite material, making it stronger, and can effectively inhibit the formation of cracks even during the process of volume expansion.
[0115] Furthermore, due to the optimization of the content of silicon dioxide, the decrease in the initial capacity and initial efficiency of the lithium secondary battery can be suppressed, and the cycle characteristics can be improved by increasing the strength of the matrix.
[0116] Specifically, according to the embodiment, based on the total weight of the silicon-carbon composite material, the silicon-carbon composite material may include 0.3% to 6% by weight, preferably 0.3% to 5% by weight, more preferably 0.5% to 5% by weight, and most preferably 1% to 4% by weight of silicon dioxide. If the content of silicon dioxide is less than the above range, the effect of improving the cycle characteristics of the lithium secondary battery may not be significant. If it exceeds the above range, it may be difficult to achieve the desired molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material, and the cycle characteristics or discharge capacity of the lithium secondary battery may deteriorate.
[0117] carbon
[0118] The silicon-carbon composite material according to the embodiment includes carbon.
[0119] According to the embodiment, since the silicon-carbon composite material contains carbon, sufficient conductivity of the silicon-carbon composite material can be ensured, and the specific surface area can be appropriately adjusted. Therefore, when it is used as a negative electrode active material of a lithium secondary battery, the life characteristics and capacity of the lithium secondary battery can be improved.
[0120] Generally, the conductivity of the negative electrode active material is an important factor in promoting electron transfer during electrochemical reactions. If the composite material as the negative electrode active material does not contain carbon, the conductivity may not reach an appropriate level.
[0121] In the silicon-carbon composite material, carbon may exist on the surface of silicon particles included in the silicon-carbon composite material. In addition, carbon may exist on the surface or inside of silicon agglomerates included in the silicon-carbon composite material.
[0122] Furthermore, carbon can act as a matrix, and silicon particles and pores can be dispersed in the composite matrix.
[0123] Specifically, the silicon-carbon composite material may have a sea-island structure, in which silicon particles or closed pores (v) form islands and carbon forms seas. The pores may be open pores and closed pores. The closed pores may include pores whose interiors are not coated with carbon.
[0124] The uniform dispersion of silicon particles or carbon was confirmed by image observation of a dark field image or a bright field image using a transmission electron microscope (TEM).
[0125] According to an embodiment, the silicon-carbon composite material includes a silicon composite material and a carbon layer on a surface thereof. Specifically, the silicon-carbon composite material includes a silicon composite material containing silicon particles, and it may include a carbon layer including carbon on a surface thereof.
[0126] In particular, since the silicon-carbon composite material includes a carbon layer, it is possible to enhance electrical contact between particles and provide excellent electrical conductivity even after the electrode expands during charging and discharging, so that the performance of the lithium secondary battery can be further improved.
[0127] Furthermore, according to the embodiment, the thickness of the carbon layer or the amount of carbon may be controlled, so that appropriate conductivity may be achieved and lifetime characteristics may be prevented from being deteriorated, thereby obtaining a negative electrode active material having a high capacity.
[0128] Based on the total weight of the silicon-carbon composite material, the content of carbon (C) may be 18 wt % to 60 wt %. Specifically, based on the total weight of the silicon-carbon composite material, the content of carbon (C) may preferably be 20 wt % to 55 wt %, 20 wt % to 50 wt % or 25 wt % to 45 wt %.
[0129] Specifically, when the silicon-carbon composite material has a core-shell structure, the content of carbon (C) may be the sum of the content of carbon (C) in the core and the amount of carbon (C) in the carbon layer included in the outer shell.
[0130] If the content of carbon (C) is less than the above range, it is not possible to expect a sufficient effect of improving conductivity, and there is a concern that the electrode life of the lithium secondary battery may deteriorate. In addition, if the content of carbon (C) exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, and the volume density may decrease, so that the charge and discharge capacity per unit volume may deteriorate.
[0131] In addition, the silicon-carbon composite material contains carbon inside the core, and based on the total weight of the silicon-carbon composite material, the content of carbon (C) inside the core of the silicon-carbon composite material can be 16 wt % to 45 wt %, preferably 18 wt % to 40 wt %, and more preferably 20 wt % to 40 wt %.
[0132] When the content of carbon (C) inside the core of the silicon-carbon composite material satisfies the above range, sufficient conductivity can be obtained, thereby further improving the electrical conductivity. Therefore, a secondary battery having excellent charge and discharge capacity and cycle characteristics can be obtained.
[0133] Furthermore, the amount of carbon (C) in the carbon layer included in the outer shell may be 2 to 10 wt %, preferably 2 to 8 wt %, and more preferably 3 to 6 wt %, based on the total weight of the silicon-carbon composite material.
[0134] According to the embodiment, the carbon in the kernel may include at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, reduced graphene oxide and carbon nanotubes, such as amorphous carbon. In this case, the interface resistance between the silicon particles and the carbon layer on the kernel surface is reduced, and the embedding and de-embedding of lithium are smoothly achieved, thereby ensuring the high output characteristics of the lithium secondary battery.
[0135] In addition, the amorphous carbon inside the core can serve as a support for fixing silicon particles, inhibiting the volume change of silicon particles during charging and discharging, and effectively blocking the contact between silicon particles and the electrolyte.
[0136] Furthermore, the outer shell may include a carbon layer (first carbon layer) including at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, reduced graphene oxide, and carbon nanotube.
[0137] Meanwhile, the thickness of the carbon layer may be 2nm to 100nm, preferably 2nm to 80nm, and more preferably 3nm to 50nm. When the thickness of the carbon layer is equal to or greater than the lower limit of the above range, an improvement in electrical conductivity may be achieved. When it is equal to or less than the upper limit of the above range, a reduction in the capacity of the lithium secondary battery may be suppressed.
[0138] The average thickness of the carbon layer can be measured, for example, by the following steps.
[0139] First, the negative electrode active material was observed by a transmission electron microscope (TEM) at an arbitrary magnification.
[0140] For example, the magnification is preferably such that it can be confirmed with the naked eye. Subsequently, the thickness of the carbon layer is measured at any 15 points. In this case, it is preferred that the measurement positions are randomly selected as widely as possible without concentrating on a specific area. Finally, the average value of the thickness of the carbon layer at the 15 points is calculated.
[0141] Porosity
[0142] The silicon-carbon composite material may include pores on its surface, in its interior, or on its surface and in its interior.
[0143] When the silicon-carbon composite material includes pores, volume expansion of silicon particles that may occur during charging and discharging of a secondary battery may be accommodated through the pores, thereby effectively alleviating and suppressing problems caused by the volume expansion.
[0144] In this specification, pores may be used interchangeably with voids. In addition, pores may include internal pores (also called closed pores) and / or internal pores.
[0145] The inner pores refer to independent pores that are not connected to other pores because the entire wall of the pore is closed to form a closed structure.
[0146] Internal pores include internal pores and open pores. At least a portion of the pore wall may be open to form an open structure so that it can be connected to other pores, or it may not be connected. In addition, it may refer to pores exposed to the outside when it is arranged on the surface of the silicon-carbon composite material.
[0147] Meanwhile, the silicon-carbon composite material includes pores inside it, and the porosity of the silicon-carbon composite material may be 10% or less. In this case, the porosity may represent internal porosity. Specifically, the porosity may be 10% or less, specifically 0.01% to 10%, preferably 0.01% to 8%, more preferably 0.1% to 8%, and most preferably 0.5% to 5%.
[0148] If the porosity of the silicon-carbon composite material exceeds the above range, the mechanical strength is reduced due to the presence of a large number of pores in the negative electrode active material, and there is a concern that the negative electrode active material may collapse in the method for manufacturing a lithium secondary battery (e.g., in the process of mixing the negative electrode active material slurry and in the rolling step after coating). At the same time, if the porosity of the silicon-carbon composite material is less than the above range, the manufacture of the silicon-carbon composite material may be difficult.
[0149] When the porosity of the silicon-carbon composite material satisfies the above range, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized, and the high capacity and life characteristics of lithium secondary batteries can be achieved.
[0150] In addition, the volume expansion that occurs during the charging and discharging process of the lithium secondary battery can be concentrated in the pores rather than outside the negative electrode active material, thereby effectively controlling the volume expansion and improving the life characteristics of the lithium secondary battery. In addition, the electrolyte can easily penetrate into the interior of the silicon-carbon composite material, thereby improving the charging and discharging characteristics, making it possible to further improve the performance of the lithium secondary battery.
[0151] The internal pores include open pores on the surface of the silicon-carbon composite material and inner pores.
[0152] The porosity of the silicon-carbon composite material may be defined as in the following Relationship 1. The porosity may refer to internal porosity.
[0153] [Equation 1]
[0154] Porosity (%) = pore volume per unit mass / (specific volume + pore volume per unit mass)
[0155] The measurement of the porosity is not particularly limited. Depending on the embodiment, for example, it can be measured by BELSORP (BET apparatus) of BEL JAPAN using an adsorbed gas (eg, nitrogen) or by a mercury penetration method (Hg porosimeter).
[0156] However, in the present invention, it may be difficult to measure an accurate value using a nitrogen adsorption method or a mercury permeation method. This may be the case where the surface of the composite material is closed by a carbon coating so that nitrogen cannot reach the inner pores. In this case, the porosity (i.e., the internal porosity) can be obtained by adding the value obtained by the adsorption gas (e.g., nitrogen) (BET) or mercury permeation method to the internal porosity of the following relational formula 2.
[0157] [Equation 2]
[0158] Internal porosity (%) = {1-(measured density / calculated density)} × 100
[0159] In relation 2, the measured density can be measured using helium.
[0160] In silicon-carbon composites, when the inner pores are closed and nitrogen or mercury cannot reach the inner pores, the porosity measured by the nitrogen adsorption method can be considered to be close to the open porosity.
[0161] According to the embodiment, after the carbon layer is formed (after carbon coating), most of the pores formed after etching may exist in a smaller amount or hardly exist.
[0162] Specifically, in the method for preparing the silicon-carbon composite material described below, when the carbon layer is formed, the pores existing inside the composite material or inside and on the surface thereof may be filled with a large amount of carbon. Therefore, the silicon-carbon composite material may include only a small amount of pores.
[0163] In addition, the amount of pores (e.g., porosity) of the silicon-carbon composite material can be controlled by adjusting the etching conditions (e.g., etching solution, its concentration, and etching time) in the method for preparing the silicon-carbon composite material described below and by changing the gas type and coating temperature during the carbon coating process to control the coating amount of carbon. Through the above-mentioned adjustment, the silicon-carbon composite material can include only a small amount of pores or almost no pores in its interior.
[0164] Meanwhile, the internal porosity of the silicon-carbon composite material may be 0.01% to 8%, preferably 0.1% to 6%, and more preferably 0.5% to 5%. The internal porosity may be calculated by the above equation 2.
[0165] When the internal porosity and the inner porosity of the silicon-carbon composite material each satisfy the above range, when it is applied to the negative electrode active material of a lithium secondary battery, a buffering effect of volume expansion can be obtained while maintaining sufficient mechanical strength. Therefore, the problem of volume expansion caused by the use of silicon particles can be minimized, and high capacity and life characteristics can be optimally promoted.
[0166] The silicon-carbon composite material can have various structures.
[0167] Specifically, the silicon-carbon composite material has a core-shell structure, and includes a silicon-carbon composite material (1) having a single-layer structure in which the outer shell is composed of a first carbon layer, a silicon-carbon composite material (2) having a multi-layer structure in which the outer shell includes at least two carbon layers (including a first carbon layer and a second carbon layer), and a combination thereof.
[0168] The properties of the silicon-carbon composite material (1) and the silicon-carbon composite material (2) are described in detail below.
[0169] Silicon Carbon Composite Materials(1)
[0170] The silicon-carbon composite material (1) according to the embodiment may be a silicon-carbon composite material having a core-shell structure in which the outer shell has a single-layer structure consisting of a first carbon layer.
[0171] The structure of the core of the silicon-carbon composite material (1), each component and its characteristics are as described above.
[0172] The first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, reduced graphene oxide, and carbon nanotube.
[0173] Specifically, the first carbon layer may use a component of the same type and nature as the first carbon layer of the silicon-carbon composite material (2) described below.
[0174] The first carbon layer may be present on the surface of the inner core.In addition, the first carbon layer may be present on the surface of the silicon particles and / or silicon agglomerates.
[0175] Furthermore, the shell is a structure surrounding the core, and the first carbon layer contained therein can suppress expansion of the core and growth of silicon particles (silicon crystals) in the core, and further improve electrical conductivity.
[0176] Based on the total weight of the silicon-carbon composite material (1), the content of carbon (C) in the silicon-carbon composite material (1) can be 18% by weight to 60% by weight, 20% by weight to 55% by weight, 20% by weight to 50% by weight or 25% by weight to 45% by weight. If the content of carbon (C) is less than the above range, it is not possible to expect a sufficient effect of improving conductivity, and it is feared that the electrode life of the lithium secondary battery may deteriorate. In addition, if the content of carbon (C) exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, and the volume density may decrease, so that the charge and discharge capacity per unit volume may deteriorate.
[0177] Furthermore, the amount of carbon (C) in the first carbon layer in the outer shell may be 2 to 10 wt %, preferably 2 to 8 wt %, and more preferably 3 to 6 wt %, based on the total weight of the silicon-carbon composite material (1).
[0178] When the amount of carbon (C) in the first carbon layer satisfies the above range, the desired effect can be effectively achieved.
[0179] The thickness of the first carbon layer may be 2 nm to 80 nm, preferably 3 nm to 50 nm, and more preferably 3 nm to 30 nm.
[0180] If the thickness of the first carbon layer is less than the above range, the conductivity of the first carbon layer is too low; therefore, when it is applied to the negative electrode active material, there may be a problem that the reactivity with the electrolyte increases and the initial efficiency of the secondary battery deteriorates. In addition, the effect of suppressing the volume expansion of silicon particles and the capacity improvement may not be significant, and a uniform coating may not be obtained. In addition, if the thickness of the first carbon layer exceeds the above range, the mobility of lithium ions may be hindered, thereby increasing the resistance, and the bonding strength with the core may deteriorate.
[0181] Silicon Carbon Composite Materials(2)
[0182] The silicon-carbon composite material (2) according to the embodiment may be a silicon-carbon composite material having a core-shell structure, wherein the shell has a multilayer structure including at least two carbon layers including a first carbon layer and a second carbon layer.
[0183] The structure of the core of the silicon-carbon composite material (2), each component and its characteristics are as described above.
[0184] The outer shell of the silicon-carbon composite material (2) may include at least two carbon layers, wherein the carbon layers include a first carbon layer and a second carbon layer formed on the first carbon layer.
[0185] The first carbon layer may be present on the surface of the inner core.In addition, the first carbon layer may be present on the surface of the silicon particles and / or silicon agglomerates.
[0186] The first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor graphene, reduced graphene oxide, and carbon nanotubes. Here, chemical vapor graphene refers to graphene formed by chemical thermal decomposition deposition (chemical vapor deposition, CVD).
[0187] Specifically, the first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, and chemical vapor graphene. For example, when amorphous carbon or crystalline carbon is arranged on the core to form the first carbon layer, the strength of the first carbon layer is properly maintained, and the expansion of the core and the growth of silicon crystals in the core can be suppressed. In addition, when crystalline carbon is arranged on the core to form the first carbon layer, the conductivity of the negative electrode active material can be further improved.
[0188] For example, when the carbon inside the inner core and the first carbon layer on the inner core surface include amorphous carbon, it is preferred that the thickness of the first carbon layer is 2 nm or more or 3 nm or more.
[0189] If the thickness of the first carbon layer is less than the above range, the effect of suppressing the volume change may not be significant, and the volume change caused by charging and discharging may increase, thereby deteriorating the cycle performance of the lithium secondary battery.
[0190] In particular, according to the embodiment, when the carbon inside the inner core and the first carbon layer on the inner core surface include amorphous carbon, due to the low crystallinity, the buffering properties relative to volume expansion are further improved, and the conductivity is further improved, so that the output characteristics and cycle characteristics of the secondary battery can be further improved.
[0191] The amorphous carbon may include a material selected from the group consisting of soft carbon (low temperature calcined carbon), hard carbon, pitch carbide, mesophase pitch carbide, calcined coke, and combinations thereof.
[0192] In addition, in the Raman spectrum obtained by Raman spectroscopy of the silicon-carbon composite material (1) in which the first carbon layer on the surface of the core includes amorphous carbon, when -1 Up to 1400cm -1 The intensity of the D band peak that appears in the range of -1 Up to 1660cm -1 When the intensity of the G band peak appearing in the range of is IG, the following relationship 3 is satisfied.
[0193] [Equation 3]
[0194] ID / IG>3
[0195] ID / IG may preferably be 3-5, more preferably 3-4.
[0196] The G band peak is a Raman shift peak of about 1550 cm-1 To about 1610cm -1 (For example, about 1580cm -1 ) and it may be a peak attributed to graphite. In addition, the D band peak is a Raman shift of about 1290 cm -1 About 1350cm -1 (For example, about 1320cm -1 ), and it may be a peak attributed to amorphous carbon.
[0197] That is, the value of ID / IG can represent the ratio of amorphous carbon to graphite in the carbon layer. In addition, the value of ID / IG represents the crystallinity of the carbon layer. A higher value of ID / IG can represent a higher proportion of amorphous carbon.
[0198] If ID / IG is smaller than the above range, the cycle characteristics of the secondary battery may be deteriorated.
[0199] The Raman spectrum was measured at a laser wavelength of 780 nm using a micro Raman spectrometer (Nicolet Almega GaXr manufactured by Thermo Fisher Scientific).
[0200] In the Raman spectrum of the first carbon layer, the intensities of the D band peak and the G band peak can be obtained as follows.
[0201] The Raman spectrum (which consists of the sum of the D band peak and the G band peak) is divided into two peaks fitted with a Gaussian function or a Gaussian / Lorentzian mixed function using a nonlinear least squares method. The integrated intensity of the obtained D band and G band is obtained, and the peak intensities of the two separated D band peaks and G band peaks are calculated respectively.
[0202] Meanwhile, the crystalline carbon may include natural graphite, artificial graphite, expandable graphite, graphene, carbon black, fullerene soot, or a combination thereof, but is not limited thereto.
[0203] The natural graphite may be naturally produced graphite, and may include flake graphite, highly crystalline graphite, microcrystalline graphite, cryptocrystalline (amorphous) graphite, and the like.
[0204] Artificial graphite is artificially synthesized graphite and is made by heating amorphous carbon at high temperatures. It can be primary graphite, electrochemical graphite, secondary graphite, graphite fiber, etc. Expandable graphite is made by inserting chemicals (such as acid or alkali) between layers and heating them to solidify the vertical layers of the molecular structure. Graphene refers to a single layer of graphite.
[0205] The second carbon layer may be present on the first carbon layer.
[0206] The second carbon layer may include at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, reduced graphene oxide, and carbon nanotube. In this case, the first carbon layer and the second carbon layer include different types.
[0207] According to an embodiment, in the silicon-carbon composite material (2), the first carbon layer may include at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, and carbon nanotube, and the second carbon layer may include reduced graphene oxide (RGO).
[0208] Reduced graphene oxide may be formed by partially reducing or substantially completely reducing graphene oxide.
[0209] When the second carbon layer includes reduced graphene oxide, it can act as a barrier layer or a buffer layer, and the buffer layer is effective as a mechanical buffer support around the core and can improve adhesion with the binder. More specifically, the buffer layer can inhibit degradation, cracking, and volume expansion of the core caused by mechanical expansion of silicon during charging and discharging.
[0210] When the silicon-carbon composite material (2) is used as a negative electrode active material, the contact resistance between the negative electrode active material layer and the current collector and the contact resistance between the negative electrode active material particles can be reduced, thereby improving lithium insertion and extraction characteristics.
[0211] Furthermore, the second carbon layer may further include graphite.
[0212] According to the embodiment, in the silicon-carbon composite material, a first carbon layer and a second carbon layer may be sequentially disposed on the core to form an outer shell.
[0213] The first carbon layer may be formed using chemical thermal decomposition deposition (chemical vapor deposition, CVD). The second carbon layer may be formed using one or more methods selected from a liquid coating method and a spray drying method.
[0214] Specifically, in the silicon-carbon composite material (2), a first carbon layer can be formed on the inner core by chemical thermal decomposition deposition, and then a second carbon layer including reduced graphene oxide can be formed on the first carbon layer using one or more methods selected from a liquid coating method and a spray drying method.
[0215] When the first carbon layer is formed on the inner core by chemical thermal decomposition deposition, the carbon (carbon layer) can be mainly formed in the pores of the inner core. Since the carbon is uniformly formed in the inner pores, the volume expansion of silicon during charging and discharging and the formation of larger silicon particles caused by the sintering of nano-silicon caused by the volume expansion can be minimized.
[0216] Meanwhile, when a second carbon layer including reduced graphene oxide is formed on the first carbon layer using at least one method selected from a liquid coating method and a spray drying method, the carbon content can be easily controlled according to the purpose, and a low specific surface area, high conductivity, high capacity and long life can be achieved.
[0217] In the silicon-carbon composite material (2), the carbon layer forming the outer shell can be laminated in various ways as long as the desired effect is not impaired. It can be up to four layers, specifically two to four layers, preferably two to three layers, for example two layers.
[0218] When a silicon-carbon composite material (2) having at least two carbon layers sequentially formed on the entire, most or part of the surface of the inner core is used as a negative electrode active material, the release of lithium in the inner core can be suppressed, and the volume change of silicon particles occurring during the insertion and extraction of lithium can be suppressed, thereby maintaining high conductivity and the conduction path between the particles of the negative electrode active material. Therefore, a negative electrode active material and a lithium secondary battery having high charge and discharge capacity and excellent cycle life characteristics can be provided.
[0219] The content of carbon (C) contained in the silicon-carbon composite material (2) may be 18 wt % to 60 wt %, 20 wt % to 60 wt %, 20 wt % to 55 wt % or 30 wt % to 55 wt % based on the total weight of the silicon-carbon composite material (2).
[0220] If the content of carbon (C) in the silicon-carbon composite material (2) is less than the above range, the effect of suppressing the volume expansion of the negative electrode active material and improving its conductivity may not be significant. If it exceeds the above range, there may be a problem that the capacity of the secondary battery may be reduced and lithium ions may be difficult to separate.
[0221] The content of carbon (C) contained in the core of the silicon-carbon composite material (2) may be the content of carbon (C) contained in the core of the silicon-carbon composite material.
[0222] In addition, in the outer shell of the silicon-carbon composite material (2), the amount of carbon (C) in the first carbon layer can be 2 weight % to 10 weight %, preferably 2 weight % to 8 weight %, and more preferably 3 weight % to 6 weight %, based on the total weight of the silicon-carbon composite material (2).
[0223] In addition, in the outer shell of the silicon-carbon composite material (2), the amount of carbon (C) in the second carbon layer can be 2 weight % to 10 weight %, preferably 2 weight % to 8 weight %, more preferably 2 weight % to 6 weight %, and even more preferably 2 weight % to 5 weight %, based on the total weight of the silicon-carbon composite material (2).
[0224] If the content of carbon (C) in the second carbon layer is less than the above range, there may be a problem that the effect of suppressing the volume expansion of the negative electrode active material and improving its conductivity may not be significant. If it exceeds the above range, there may be a problem that the capacity of the secondary battery may be reduced and lithium ions may be difficult to separate.
[0225] Specifically, the shell allows lithium to pass through, but prevents oxygen from passing through. It can prevent oxygen from reacting with silicon and / or silicon oxide compounds in the kernel. In addition, if the shell is uniformly coated to form on the kernel, it has the effect of suppressing cracks caused by stress caused by the rapid volume expansion of silicon. Since the cracks are formed irregularly and discontinuously, the electrolyte may not be in contact with the inside of the negative electrode active material, or there may be a portion of resistance plugging, which can cause defects in the secondary battery. In this regard, the role of the reduced graphene oxide of the second carbon layer is of great significance. Since the reduced graphene oxide has a high electrical conductivity, the state of the carbon layer being electrically connected can be maintained.
[0226] At the same time, the total thickness of the first carbon layer and the second carbon layer can be 5nm to 100nm, preferably 5nm to 80nm, and more preferably 5nm to 50nm. When the total thickness of the first carbon layer and the second carbon layer meets the above range, even if the volume of the core changes due to the insertion and extraction of lithium, the powdering of the core can be effectively prevented or alleviated, and the side reaction between silicon and the electrolyte can be effectively prevented or alleviated, thereby improving the performance of the secondary battery.
[0227] Specifically, the thickness of the first carbon layer may be 2 nm to 50 nm, preferably 2 nm to 40 nm, and more preferably 3 nm to 30 nm. If the thickness of the first carbon layer is less than the above range, the conductivity of the first carbon layer is too low; therefore, when it is applied to the negative electrode active material, there may be a problem of increased reactivity with the electrolyte and deterioration of the initial efficiency of the secondary battery. In addition, the effect of suppressing the volume expansion of silicon particles and increasing the capacity may not be significant, and a uniform coating may not be obtained. In addition, if the thickness of the first carbon layer exceeds the above range, the mobility of lithium ions may be hindered, thereby increasing the resistance, and the bonding strength of the core may deteriorate.
[0228] The thickness of the second carbon layer may be 3 nm to 50 nm, preferably 3 nm to 30 nm, and more preferably 5 nm to 20 nm. If the thickness of the second carbon layer is less than the above range, the conductivity of the second carbon layer is too low; therefore, when it is applied to the negative electrode active material, there may be a problem of increased reactivity with the electrolyte and deterioration of the initial efficiency. In addition, the effect of suppressing the volume expansion of silicon particles and increasing the capacity may not be significant, and a uniform coating may not be obtained. If the thickness of the second carbon layer exceeds the above range, the thickness of the second carbon layer is too thick, the mobility of lithium ions may be hindered, thereby increasing the resistance, and the bonding strength of the core may deteriorate.
[0229] In the silicon-carbon composite material (2), it is preferred that the carbon layer including at least two carbon layers is formed so that each carbon layer is thinly and uniformly formed along the entire outer shape of the outer shell while maintaining the outer shape of the outer shell. However, the carbon layer may be in a form in which a part or most of the entire surface of the inner core is covered. When each of the first carbon layer and the second carbon layer is thinly and uniformly formed on the surface of the inner core, the electrical contact between the particles contained in the negative electrode active material can be improved.
[0230] The specific surface area (Brunauer-Emmett-Teller; BET) of the silicon-carbon composite material (2) may be 2 m 2 / g to 30m 2 / g,2m 2 / g to 20m 2 / g or 2m 2 / g to 10m 2 / g.
[0231] In addition, in the Raman spectrum of the silicon-carbon composite material (2) obtained by Raman spectroscopy, when -1 Up to 2760cm -1 The intensity of the 2D band peak that appears in the range of 1500 cm is I2D. -1 Up to 1660cm -1 The intensity of the G band peak that appears in the range of IG is 1280cm -1 Up to 1400cm -1 When the intensity of the D band peak appearing in the range of is ID, the following relationship 4 is satisfied.
[0232] [Equation 4]
[0233] 0.5<(I2D+IG) / ID≤2.0
[0234] In addition, based on the total weight of the reduced graphene oxide, the content of oxygen (O) in the reduced graphene oxide in the second carbon layer may be 0.5 wt % to 10 wt %, preferably 1 wt % to 10 wt %, and more preferably 3 wt % to 10 wt %. When the content of oxygen (O) in the reduced graphene oxide in the second carbon layer satisfies the above range, the degree of reduction of the graphene oxide increases, thereby reducing the graphene oxide with high conductivity can be obtained; therefore, the effect of the lithium secondary battery can be further improved.
[0235] The reduced graphene oxide in the second carbon layer may contain at least one selected from lithium (Li), sodium (Na) and potassium (K) in an amount of 0.1 wt % to 5 wt %, preferably 0.1 wt % to 4 wt %, more preferably 0.1 wt % to 3 wt %, based on the total weight of the carbon (C) in the second carbon layer. When the reduced graphene oxide in the second carbon layer contains at least one selected from lithium (Li), sodium (Na) and potassium (K) in the above content, it is even more advantageous to achieve the desired effect.
[0236] The electrode expansion rate of the silicon-carbon composite material (2) is 50% to 150%, preferably 50% to 100%, and more preferably 55% to 80%, based on the thickness of the electrode after one charge and discharge cycle.
[0237] The silicon-carbon composite material (2) includes at least two carbon layers (including a first carbon layer and a second carbon layer), thereby further improving the strength of the outer shell layer, enhancing the bonding (adhesion) between the silicon-carbon composite material (2) and the adhesive, resulting in a reduced electrode expansion rate, and improving the capacity retention rate of the lithium secondary battery after cycling (for example, after 100 cycles).
[0238] [Method for preparing silicon-carbon composite material]
[0239] The method for preparing a silicon-carbon composite material according to the embodiment includes a first step of etching a silicon-based raw material powder using an etching solution containing a compound containing fluorine (F) atoms; a second step of filtering and drying the product obtained by etching to prepare a silicon composite material; and a third step of coating carbon on the interior of the silicon composite material using a chemical thermal decomposition deposition method or coating carbon on the interior of the silicon composite material and forming a carbon layer on its surface to obtain a silicon-carbon composite material.
[0240] Specifically, in the method for preparing the silicon-carbon composite material, the first step may include etching the silicon-based raw material powder using an etching solution containing a compound containing fluorine (F) atoms.
[0241] The silicon-based raw material powder may include a silicon-containing powder capable of reacting with lithium, for example, a powder containing two or more of silicon, silicon oxide, and silicon dioxide.
[0242] The etching step may include dry etching and wet etching.
[0243] If dry etching is used, selective etching can be performed.
[0244] The silicon dioxide of the silicon-based raw material powder is dissolved and eluted by the etching step, thereby forming pores.
[0245] Furthermore, the pores can be considered to be formed by the following reaction formulas 2 and 3.
[0246] [Reaction 2]
[0247] SiO2+4HF(gas)→SiF4+2H2O
[0248] [Reaction 3]
[0249] SiO2+6HF(aqueous solution)→H2SiF6+2H2O
[0250] Pores (voids) may be formed at locations where silicon dioxide is dissolved and removed in the form of SiF4 and H2SiF6 by a reaction mechanism as in the above-described reaction formula.
[0251] Furthermore, depending on the degree of etching, silicon dioxide contained in the silicon composite material may be removed, and pores may be formed therein.
[0252] Here, etching refers to a process of treating silicon-based raw material powder using an etching solution containing a compound containing fluorine (F) atoms.
[0253] As the etching solution containing the compound containing fluorine (F) atoms, a commonly used etching solution containing fluorine atoms may be used without limitation within a range not impairing the effects.
[0254] Specifically, the compound containing fluorine (F) atoms may include at least one selected from HF, NH 4 F, and HF 2. Since the compound containing fluorine (F) atoms is used, the etching step may be performed more quickly.
[0255] The etching solution may further include one or more acids selected from organic acids, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, and chromic acid.
[0256] As etching conditions, the stirring temperature (processing temperature) may be, for example, 10°C to 90°C, preferably 10°C to 80°C, and more preferably 20°C to 70°C.
[0257] The silicon composite material may have a portion remaining silicon oxide and a portion remaining silicon dioxide.
[0258] Specifically, the content of silicon dioxide in the silicon composite material may be 0.1 wt % to 5 wt %, preferably 0.2 wt % to 5 wt %, and more preferably 0.5 wt % to 4 wt %. A negative electrode active material comprising a composite material containing silicon dioxide in the above range is preferred because its charge and discharge cycle characteristics are good and a lithium secondary battery with a high battery capacity can be provided.
[0259] In addition, the amount of oxygen present on the surface of the silicon composite material can be reduced by etching. That is, by etching, the oxygen fraction on the surface of the silicon composite material can be significantly reduced and the surface resistance can be reduced. Therefore, when the silicon-carbon composite material is applied to the negative electrode active material, the electrochemical properties of the lithium secondary battery, especially the life characteristics, can be significantly improved.
[0260] According to the embodiment, since silicon dioxide is removed by etching to significantly reduce oxygen concentration, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon composite material and the silicon-carbon composite material may be significantly reduced.
[0261] At the same time, pores may be formed in the portion where silicon dioxide is removed by etching. Specifically, the silicon composite material after etching and before carbon coating may be porous.
[0262] Furthermore, it is characterized in that the average particle diameter of the silicon composite material is hardly changed by etching.
[0263] In addition, according to the desired purpose, selective etching can be performed. Since selective etching removes a large amount of silicon dioxide, it can contain a very high fraction of silicon (Si) compared to oxygen (O). In particular, the surface of the etched silicon particles can contain a very low fraction of oxygen (O) compared to silicon (Si). In this case, a lithium secondary battery with excellent capacity retention and improved discharge capacity and initial efficiency can be obtained.
[0264] In the method for preparing a silicon-carbon composite material, the second step may include filtering and drying the product obtained by etching to obtain the silicon composite material. The filtering and drying steps may be performed by common methods.
[0265] In the method for preparing the silicon-carbon composite material, the third step may include forming a first carbon layer on the surface of the silicon composite material using a chemical thermal decomposition deposition method to obtain the silicon-carbon composite material.
[0266] By forming the carbon layer in the third step, the electrical contact between the silicon-carbon composite material particles can be enhanced. In addition, excellent conductivity can be achieved even after the electrode expands as charging and discharging proceeds, making it possible to further improve the performance of the lithium secondary battery.
[0267] Specifically, the carbon layer can improve the conductivity of the negative electrode active material, thereby improving the output characteristics and cycle characteristics of the battery, and can improve the stress relaxation effect when the volume of the active material changes.
[0268] The carbon layer may include at least one selected from graphene, reduced graphene oxide, carbon nanotubes, carbon nanofibers, and graphite.
[0269] The formation of the carbon layer in the third step may be performed by injecting at least one selected from the compounds represented by the following Formulae 1 to 3 and reacting in a gaseous state at 400° C. to 1200° C.:
[0270] [Formula 1]
[0271] C N H (2N+2-A) [OH] A
[0272] In Formula 1, N is an integer from 1 to 20, A is 0 or 1,
[0273] [Formula 2]
[0274] C N H (2N-B)
[0275] In Formula 2, N is an integer from 2 to 6, B is an integer from 0 to 2,
[0276] [Formula 3]
[0277] C x H y O z
[0278] In Formula 3, x is an integer of 1 to 20, y is an integer of 0 to 25, and z is an integer of 0 to 5.
[0279] For example, the third step may include forming carbon in the inner core and forming a first carbon layer in the outer shell by injecting at least one selected from compounds represented by the following Formulae 1 to 3 and reacting in a gaseous state at 400 to 1200° C.
[0280] That is, when the third step is performed, a silicon-carbon composite material (1) having a core-shell structure can be obtained, in which the core contains silicon particles and carbon, and the shell includes a carbon layer (first carbon layer).
[0281] The compound represented by Formula 1 may be at least one selected from methane, ethane, propane, butane, methanol, ethanol, propanol, propylene glycol and butanediol. The compound represented by Formula 2 may be at least one selected from ethylene, acetylene, propylene, butylene, butadiene and cyclopentene. The compound represented by Formula 3 may be at least one selected from benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene and butylated hydroxytoluene (BHT).
[0282] In addition, the carbon coating layer can be uniformly formed on the surface of the pores inside the silicon-carbon composite material. This is preferable because the cycle life is further improved.
[0283] The carbon source gas may further include at least one inert gas selected from hydrogen, nitrogen, helium and argon.For example, the reaction may be performed at 400 to 1200°C, particularly 500 to 1100°C, and more particularly 600 to 1000°C.
[0284] The reaction time (or heat treatment time) can be appropriately adjusted according to the heat treatment temperature, the pressure during the heat treatment, the composition of the gas mixture, and the desired amount of carbon coating. For example, the reaction time can be 10 minutes to 100 hours, particularly 30 minutes to 90 hours, and more particularly 50 minutes to 40 hours, but it is not limited thereto.
[0285] In the method for preparing a silicon-carbon composite material according to the embodiment, a thin and uniform carbon layer can be formed on the surface of the silicon composite material by a gas phase reaction of a carbon source gas even at a relatively low temperature, and the carbon layer includes amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor graphene, reduced oxide graphene or carbon nanotubes as a main component. In addition, a separation reaction does not substantially occur in the carbon layer thus formed.
[0286] Furthermore, since carbon is uniformly formed inside the silicon composite material and on the entire surface thereof by a gas phase reaction, a carbon thin film (carbon layer) having high crystallinity can be formed.
[0287] Therefore, when the silicon-carbon composite material is used as a negative electrode active material, the conductivity of the negative electrode active material can be improved without changing the structure.
[0288] In addition, according to the embodiment, when a reaction gas containing a carbon source gas and an inert gas is supplied to the silicon composite material, the reaction gas penetrates into the open pores of the silicon composite material and grows a conductive carbon material on the surface of the silicon composite material, such as one or more graphene-containing materials selected from graphene, reduced graphene oxide, graphene oxide, carbon nanotubes and carbon nanofibers.
[0289] For example, as the reaction time passes, the conductive carbon material deposited on the surface of silicon in the silicon composite material gradually grows to obtain the silicon-carbon composite material.
[0290] Meanwhile, according to the embodiment, the specific surface area of the silicon-carbon composite material may be reduced according to the amount of carbon coating.
[0291] The structure of the graphene-containing material may be a layer, a nanosheet type, or a structure in which multiple fragments are mixed.
[0292] If a carbon layer including a graphene-containing material is uniformly formed on the entire surface of the silicon composite material, volume expansion can be suppressed because the graphene-containing material having improved conductivity and flexibility to volume expansion is grown directly on the surface of the silicon particles. In addition, the coating of the carbon layer can reduce the chance of direct contact of silicon with the electrolyte, thereby reducing the formation of a solid electrolyte interface (SEI) layer. In addition, the carbon present in the silicon-carbon composite material can be uniformly present inside and / or on the surface of the composite material.
[0293] According to the embodiment, the step of forming the carbon coating makes most of the open pores and closed pores present inside and on the surface of the silicon composite material filled with carbon. Therefore, the porosity of the silicon-carbon composite material can be significantly reduced. In other words, the silicon-carbon composite material may not have pores, or may have a small amount of pores. For example, since the silicon-carbon composite material has almost no pores, the strength and density of the silicon-carbon composite material are improved, which can improve the discharge capacity per volume of the lithium secondary battery.
[0294] If pores are present in the silicon-carbon composite material after carbon coating, the porosity is as described above.
[0295] In addition, according to the embodiment, the silicon carbon composite material may have a three-dimensional (3D) structure in which silicon carbon composite material particles are bonded to each other.
[0296] Meanwhile, the method for preparing a silicon-carbon composite material according to the embodiment may further include a fourth step of forming a second carbon layer on the first carbon layer using a liquid coating method after forming the first carbon layer.
[0297] In the method for preparing a silicon-carbon composite material, when it includes the first step to the third step, a silicon-carbon composite material (1) including a first carbon layer can be obtained, and when it includes the first step to the fourth step, a silicon-carbon composite material (2) including a first carbon layer and a second carbon layer can be obtained.
[0298] Specifically, refer again to Figure 1 , Figure 1 The silicon composite material of (B) can be obtained through a first step of etching and a second step of filtering and drying the product obtained by etching.
[0299] For example, Figure 1As shown in (B), the silicon composite material may include silicon particles (20) and a large number of pores (10).
[0300] Depending on the degree of etching, silicon dioxide contained in the silicon composite material may be removed, and pores may be formed therein.
[0301] In addition, the amount of oxygen present on the surface of the silicon composite material can be reduced by etching. That is, by etching, the oxygen fraction on the surface of the silicon composite material can be significantly reduced and the surface resistance can be reduced. Therefore, when the silicon-carbon composite material is applied to the negative electrode active material, the electrochemical properties of the lithium secondary battery, especially the life characteristics, can be significantly improved.
[0302] at the same time, Figure 1 The silicon-carbon composite material (1) of (C) can be deposited by using the third step ( Figure 1 In this case, in the silicon-carbon composite material (1), carbon may be coated on the inside of the silicon composite material, or carbon may be coated on the inside of the silicon composite material and a carbon layer (first carbon layer) may be formed on the surface thereof.
[0303] Specifically, the silicon-carbon composite material (1) formed by the third step may include silicon particles (20), specifically silicon agglomerates in which the silicon particles (20) are bonded to each other (or connected to each other), wherein a carbon layer (first carbon layer) (40) may be formed on the surface of the silicon particles, and carbon (45) may be formed to be uniformly dispersed and / or distributed between the silicon particles (20). In addition, the silicon-carbon composite material (1) may include pores (10).
[0304] When a carbon layer (first carbon layer) is formed using a chemical thermal decomposition deposition method in the third step, most of the pores inside the silicon composite material are filled with carbon, or are uniformly coated with an amorphous carbon layer, for example, which has the advantage of suppressing the volume expansion of silicon and / or sintering of silicon during discharge.
[0305] By forming the carbon layer (first carbon layer) in the third step, the electrical contact between the particles of the silicon-carbon composite material (1) can be enhanced. In addition, excellent conductivity can be imparted as charging and discharging proceeds, even after electrode expansion, so that the performance of the secondary battery can be further improved.
[0306] In addition, you can get Figure 1 (D) The silicon-carbon composite material (2), wherein the fourth step ( Figure 1 (2)) in which a second carbon layer is formed on the first carbon layer.
[0307] Specifically, the silicon-carbon composite material (2) prepared by the fourth step may have a core-shell structure, wherein the core may contain silicon particles (20) and carbon (45), and the shell may include a first carbon layer (40) and a second carbon layer (50) on the first carbon layer (40). In addition, the silicon-carbon composite material (2) may include pores (10).
[0308] The second carbon layer may be formed using reduced graphene oxide. The reduced graphene oxide may be formed by partially reducing or substantially completely reducing graphene oxide. Specifically, when dried by a spray dryer, the second carbon layer may be formed by the reduced graphene oxide on the surface of the first carbon layer through partial π-π bonds or physical bonds between carbon-carbon layers.
[0309] The formation of the second carbon layer may be performed using one or more methods selected from a dry coating method and a liquid coating method.
[0310] Specifically, the second carbon layer can be formed by a spray drying method in a liquid coating method. When the second carbon layer is formed by the spray drying method, unlike the chemical thermal decomposition deposition method, the carbon content can be controlled by adjusting the concentration of reduced graphene oxide, and the coating is performed at a low temperature, thereby having the advantage that the crystal size of silicon caused by the carbon coating process at a high temperature does not increase.
[0311] In the formation of the second carbon layer, graphene oxide or reduced graphene oxide is dispersed in a solvent to prepare a dispersion, wherein the concentration of the dispersion may be 0.01 mg / ml to 50 mg / ml.
[0312] In addition, the temperature of the spray drying may be 100° C. to 500° C., specifically 150° C. to 350° C. In addition, when the spray drying is performed using graphene oxide at the above temperature, the graphene oxide may be reduced to form reduced graphene oxide.
[0313] That is, in the preparation of the silicon-carbon composite material (2), the first carbon layer can be formed by using a chemical thermal decomposition deposition method, and the second carbon layer can be formed by using a spray drying method.
[0314] The second carbon layer formed using the spray drying method may be heat-treated at 500° C. to 800° C. in an inert gas to adjust the oxygen content of the second carbon layer.
[0315] Meanwhile, according to the embodiment, after forming the first carbon layer or the second carbon layer in any one or more of the third step and the fourth step, a step of at least one of pulverizing and classifying the silicon-carbon composite material may be further performed to have a desired average particle size.
[0316] For example, after forming the first carbon layer in the third step, one or more silicon composite powders may be combined with each other to form agglomerates, and the method may further include pulverizing and classifying the silicon-carbon composite material so that its average particle diameter is 2 μm to 15 μm. Classification may be performed to adjust the particle size distribution of the silicon-carbon composite material, for which dry classification, wet classification, or classification using a sieve may be used.
[0317] In dry classification, airflow is used to sequentially or simultaneously perform the steps of dispersion, separation, collection (separation of solids and gases) and discharge, wherein pretreatment (adjusting moisture, dispersibility, humidity, etc.) may be performed before classification to avoid interference between particles, particle shape, airflow disturbance, velocity distribution, static electricity, etc., which may reduce the classification efficiency, thereby adjusting the moisture or oxygen concentration in the airflow used.
[0318] Furthermore, a desired particle size distribution can be obtained by simultaneously performing pulverization and classification. After pulverization, it is effective to separate the coarse powder portion and the granular portion using a classifier or a sieve.
[0319] Specifically, after forming the first carbon layer and / or the second carbon layer, a pulverization process may be performed.
[0320] Alternatively, a step (fifth step) of performing at least one step of pulverizing and classifying the silicon-carbon composite material having a core-shell structure obtained in the fourth step may be further performed.
[0321] According to the embodiment, when the silicon-carbon composite material having a core-shell structure is pulverized and / or classified, a silicon-carbon composite material having a desired average particle size may be obtained.
[0322] Specifically, in the fifth step, the silicon-carbon composite material (2) obtained in the fourth step may be classified. Alternatively, the silicon-carbon composite material (2) may be crushed. Alternatively, the silicon-carbon composite material (2) may be crushed and classified. Specifically, the silicon-carbon composite material (2) obtained in the fourth step may be classified and, if necessary, crushed. Alternatively, the silicon-carbon composite material (2) obtained in the fourth step may be crushed.
[0323] According to the above preparation method, a silicon-carbon composite material can be provided, wherein the silicon-carbon composite material comprises silicon particles and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is within a specific range. When the silicon-carbon composite material is used in a negative electrode active material to manufacture a lithium secondary battery, the discharge capacity and initial efficiency can be significantly improved, while having an excellent capacity retention rate.
[0324] In addition, since the silicon-carbon composite material includes at least one carbon layer, sufficient conductivity can be ensured and the specific surface area can be appropriately adjusted. Therefore, the performance of the lithium secondary battery can be improved. In addition, the characteristics of the secondary battery can be controlled by changing the shell structure of the silicon-carbon composite material.
[0325] In particular, the silicon-carbon composite material includes at least two carbon layers (including a first carbon layer and a second carbon layer), thereby further improving the strength, enhancing the bonding (adhesion) between the silicon-carbon composite material (2) and the binder, resulting in a reduction in the electrode expansion rate, and further improving the capacity retention rate of the lithium secondary battery after cycling.
[0326] Furthermore, the preparation method according to the embodiment is advantageous in that large-scale production can be performed through a continuous process with a minimum number of steps.
[0327] The silicon-carbon composite material prepared by the above-mentioned preparation method can be advantageously used in negative electrode active materials and lithium secondary batteries, and it can effectively achieve the desired effects.
[0328] [Negative electrode active material]
[0329] The negative electrode active material according to the embodiment may include a silicon-carbon composite material.
[0330] Furthermore, the negative electrode active material may also include a carbon-based negative electrode material, in particular a graphite-based negative electrode material.
[0331] A mixture of a silicon-carbon composite material and a carbon-based negative electrode material (eg, a graphite-based negative electrode material) can be used as a negative electrode active material. In this case, the resistance of the negative electrode active material can be reduced, and the expansion stress during charging can be relieved.
[0332] The carbon-based negative electrode material may include, for example, at least one selected from natural graphite, synthetic graphite, soft carbon, hard carbon, mesophase carbon, carbon fiber, carbon nanotube, pyrolytic carbon, coke, glass carbon fiber, sintered organic polymer compound and carbon black.
[0333] The carbon-based negative electrode material may be contained in an amount of 10 to 95 wt %, preferably 30 to 90 wt %, and more preferably 30 to 80 wt %, based on the total weight of the negative electrode active material.
[0334] Furthermore, if a silicon-carbon composite material including silicon particles having a grain size of 2 nm to 10 nm is mixed with a graphite-based material generally having low volume expansion, the silicon particles alone do not cause a large volume expansion; therefore, a lithium secondary battery having excellent cycle characteristics can be obtained.
[0335] Furthermore, the negative electrode active material may also contain silicon powder coated with carbon on the surface and a composite material composed of silicon powder and graphite.
[0336] According to an embodiment, a negative electrode including a negative electrode active material and a lithium secondary battery including the negative electrode are provided.
[0337] The lithium secondary battery may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous liquid electrolyte in which a lithium salt is dissolved, wherein the negative electrode may include a negative electrode active material including a silicon-carbon composite material.
[0338] The negative electrode may be composed only of the negative electrode mixture, or may be composed of a negative electrode current collector and a negative electrode mixture layer (negative electrode active material layer) loaded thereon. Similarly, the positive electrode may be composed only of the positive electrode mixture, or may be composed of a positive electrode current collector and a positive electrode mixture layer (positive electrode active material layer) loaded thereon. In addition, the negative electrode mixture and the positive electrode mixture may each further comprise a conductive agent and a binder.
[0339] As the material constituting the negative electrode current collector and the material constituting the positive electrode current collector, materials known in the art may be used. As the binder and the conductive material added to the negative electrode and the positive electrode, materials known in the art may be used.
[0340] If the negative electrode is composed of a current collector and an active material layer supported thereon, the negative electrode may be prepared by coating a negative electrode active material composition including a silicon-carbon composite material on the surface of the current collector and drying it.
[0341] In addition, the lithium secondary battery includes a non-aqueous liquid electrolyte, wherein the non-aqueous liquid electrolyte may include a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0342] As the non-aqueous solvent, a solvent commonly used in the art can be used. Specifically, an aprotic organic solvent can be used.
[0343] Examples of aprotic organic solvents include cyclic carbonates (e.g., ethylene carbonate, propylene carbonate, and butylene carbonate), cyclic carboxylates (e.g., furanone), chain carbonates (e.g., diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate), chain ethers (e.g., 1,2-methoxyethane, 1,2-ethoxyethane, and ethoxymethoxyethane), and cyclic ethers (e.g., tetrahydrofuran and 2-methyltetrahydrofuran). They may be used alone or in combination of two or more.
[0344] The lithium secondary battery may include a non-aqueous lithium secondary battery.
[0345] A negative electrode active material and a lithium secondary battery using the silicon-carbon composite material according to the embodiment may improve charge and discharge capacity as well as initial charge and discharge efficiency and capacity retention rate.
[0346] The present invention will be described in detail below with reference to Examples. The following Examples are only for illustrating the present invention, and the scope of the present invention is not limited thereto.
[0347] Mode for the Invention
[0348] <Example 1>
[0349] Preparation of Silicon Carbon Composite Materials
[0350] (1) Step 1: 50 g of silicon oxide (SiO2) prepared by vapor deposition using silicon powder and silicon dioxide powder and having the physical properties shown in Table 1 below x , x=1.01) powder was dispersed in 50 g of water, stirred at a speed of 300 rpm, and 110 ml of a 40 wt % HF aqueous solution was added as an etching solution to etch the silicon-based raw material powder for 1 hour.
[0351] (2) Step 2: The product obtained by the above etching was filtered and dried at 100° C. for 2 hours.
[0352] Then, in order to control the particle size of the composite material, it was pulverized using a mortar so as to have an average particle diameter of about 5 μm, thereby preparing a silicon composite material (B1).
[0353] (4) Step 3: 10 g of the silicon composite material was placed in a tubular electric furnace, and argon (Ar) and methane gas were flowed at a rate of 1 liter / minute, respectively. It was kept at 900° C. for 1 hour and then cooled to room temperature to coat the surface of the silicon composite material with carbon, thereby preparing a silicon-carbon composite material having the content and physical properties of each component as shown in Table 3 below.
[0354] In order to control the particle size of the silicon-carbon composite material, it was pulverized and classified by a mechanical method to have an average particle diameter of about 5 μm, thereby preparing a silicon-carbon composite material (1).
[0355] Manufacturing of lithium secondary batteries
[0356] A negative electrode and a battery (button cell) containing the silicon-carbon composite material (1) as a negative electrode active material were prepared respectively.
[0357] The negative electrode active material, Super-P as a conductive material, and polyacrylic acid were mixed with water at a weight ratio of 80:10:10 to prepare a negative electrode active material composition having a solid content of 45%.
[0358] The negative electrode active material composition was applied to a copper foil having a thickness of 18 μm and dried to prepare an electrode having a thickness of 70 μm. The copper foil coated with the electrode was punched into a circular shape having a diameter of 14 mm to prepare a negative electrode for a button cell.
[0359] Meanwhile, a metal lithium foil with a thickness of 0.3 mm was used as the positive electrode.
[0360] A porous polyethylene sheet with a thickness of 25 μm was used as a separator. A liquid electrolyte in which LiPF6 was dissolved at a concentration of 1 M in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 was used as an electrolyte. A button cell (battery, CR2032) was manufactured using the above components.
[0361] <Examples 2 to 7>
[0362] The same method as in Example 1 was carried out to prepare a silicon-carbon composite material (1), and the silicon-carbon composite material (1) was used to manufacture a negative electrode active material and a lithium secondary battery, except that a silicon-based raw material powder (A) and a silicon composite material (B) as shown in Tables 1 and 2 below were used, the type and amount of the carbon source gas were changed as shown in Table 3, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material was changed.
[0363] <Example 8>
[0364] A silicon-carbon composite material (2) having a second carbon layer formed on the surface of the first carbon layer of the silicon-carbon composite material (1) prepared in Example 2 using a spray dryer was obtained.
[0365] The second carbon layer was formed by spray drying in the following manner:
[0366] (1) to (3) Steps 1 to 3: The same steps as in Example 2 were performed.
[0367] (4) Step 4: The silicon-carbon composite material having the first carbon layer obtained in Example 2 was added to 0.5 wt % of graphene oxide at the same weight ratio to prepare a graphene oxide dispersion. When the dispersion was injected at 100 ml / min using a metering pump, spray drying was performed at a dispersion concentration of 1.0 mg / ml and a spray temperature of 250° C., thereby obtaining a silicon-carbon composite material having two layers (including a first carbon layer and a second carbon layer).
[0368] (5) Step 5: In order to control the particle size of the silicon-carbon composite material, the silicon-carbon composite material is crushed and classified by a mechanical method to have an average particle diameter (D 50 ), thereby preparing the final silicon-carbon composite material (2).
[0369] A negative electrode active material and a lithium secondary battery were manufactured in the same manner as in Example 1 using the silicon-carbon composite material (2).
[0370] <Example 9>
[0371] The same method as in Example 8 is carried out to prepare a silicon-carbon composite material (2), and the silicon-carbon composite material (2) is used to manufacture a negative electrode active material and a lithium secondary battery, except that a spray dryer is used on the first carbon layer of the silicon-carbon composite material (1) prepared in Example 4, and it is adjusted to have the composition and properties shown in Table 4.
[0372] <Comparative Example 1>
[0373] A negative electrode active material and a lithium secondary battery using the silicon-carbon composite material (1) were manufactured in the same manner as in Example 1, except that the etching process of step 1 using the etching solution in Example 1 was not performed.
[0374] <Comparative Examples 2 to 4>
[0375] The same method as in Example 1 was carried out to prepare a silicon-carbon composite material, and a lithium secondary battery was manufactured using the silicon-carbon composite material, except that a silicon composite material (B) having an atomic content and properties as shown in Table 2 below was used, the type and amount of the carbon source gas was changed as shown in Table 3, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material was changed.
[0376] Test Example
[0377] <Test Example 1> Electron Microscope Analysis
[0378] Figure 2 and Figure 3 Ion beam scanning electron microscope (FIB-SEM, [FC-FI20]-FIB II instrument) photographs of the silicon composite material (B1) and the silicon-carbon composite material (C1) prepared in Example 1 are respectively shown.
[0379] That is to say, Figure 2 and Figure 3 The figures show the silicon composite material (B1) and the silicon-carbon composite material (C1) analyzed by ion beam scanning electron microscopy (FIB-SEM) at a magnification of 30,000.
[0380] also, Figure 4 The ion beam transmission electron microscope (TEM-FIB) photograph of the silicon-carbon composite material (C1) prepared in Example 1 is shown. Here, the white bright spots represent Si crystals, and the black spots represent carbon (C). Figure 4It can be seen that the surface of the silicon-carbon composite material (C1) particles has a large amount of carbon, and the inside of the particles has a large amount of Si components.
[0381] <Test Example 2> X-ray Diffraction Analysis
[0382] The crystal structure of the silicon-carbon composite material prepared in the example was analyzed using an X-ray diffraction analyzer (X'Pert3 from Malvern Panalytical).
[0383] Specifically, the applied voltage was 40 kV, and the applied current was 40 mA. The range of 2θ was 10° to 80°, and the measurement was performed by scanning at an interval of 0.05°.
[0384] Figure 5 and Figure 7 The measurement results of X-ray diffraction analysis of the silicon-carbon composite materials of Examples 1 and 4 are shown respectively.
[0385] refer to Figure 5 and Figure 7 From the X-ray diffraction patterns, it can be seen that the silicon-carbon composite materials of Examples 1 and 4 have peaks corresponding to Si crystals near diffraction angles (2θ) of 28.3°, 47.5°, 56.1°, 69.1°, and 76.5° (indicating that they contain crystalline Si) and peaks near 22.5° and 50° (indicating that they contain silicon oxide (SiO x , 0.4≤x≤2)). In addition, the diffraction angle (2θ) of carbon could not be determined because it overlaps with the Si (111) peak.
[0386] <Test Example 3> Analysis of the content of each component element in the silicon composite material or silicon-carbon composite material
[0387] The content of each component element of oxygen (O) and carbon (C) in the silicon composite materials or porous silicon-carbon composite materials prepared in Examples and Comparative Examples was analyzed.
[0388] The contents of oxygen (O) and carbon (C) were analyzed by an element analyzer, respectively. The content of silicon (Si) is a value calculated based on the content of oxygen (O).
[0389] <Test Example 4> Measurement of Average Particle Diameter of Silicon Composite Material or Silicon Carbon Composite Material
[0390] The average particle diameter (D 50 ) is used as the average diameter D in the particle size distribution measurement according to the laser beam diffraction method. 50 The particle diameter or median diameter is measured when the cumulative volume is 50%.
[0391] <Test Example 5> Raman spectroscopy analysis
[0392] Raman spectroscopy analysis was performed on the silicon-carbon composite material prepared in Example 1. Raman analysis was performed using a micro Raman analyzer (Renishaw, RM1000-In Via) at 2.41 eV (514 nm). The results are shown in Figure 6 middle.
[0393] refer to Figure 6 , the G band (1580 cm -1 ) and D belt (1350cm -1 ), thereby confirming that the silicon-carbon composite material prepared in Example 1 contains carbon with electrical conductivity.
[0394] Therefore, the electrical conductivity of the silicon-carbon composite material prepared in Example 1 is excellent and can significantly improve the performance of the lithium secondary battery.
[0395] <Test Example 6> Measurement of Electrode Expansion Rate
[0396] Before electrode fabrication, the thickness (N1) of the rolled negative electrode using the negative electrode active material prepared in Example was measured.
[0397] The cycle life of a secondary battery (button cell) made using a negative electrode was measured, and the measurement was terminated at 80% of the cycle life. Subsequently, the button cell was disassembled, the negative electrode was separated, and it was immersed in a dimethyl carbonate (DMC) solvent and then taken out. Then, after the solvent was completely dried, the thickness (N2) of the side surface of the separated negative electrode was measured using SEM.
[0398] The ratio of the thickness of the rolled negative electrode before electrode manufacturing (N1) to the thickness of the negative electrode measured at 80% of the cycle life (N2) was converted into a percentage and calculated as follows:
[0399] [Equation A]
[0400] Electrode expansion rate (%) = thickness of negative electrode when measuring at 80% of cycle life (N2) / thickness of rolled negative electrode before electrode manufacturing (N1) × 100
[0401] <Test Example 7> Measurement of Capacity, Initial Efficiency and Capacity Retention Rate of Lithium Secondary Batteries
[0402] The battery was charged at a constant current of 0.1 C until the voltage reached 0.005 V, and then the current reached 0.005 C at a constant voltage. It was then discharged at a constant current of 0.1 C until the voltage reached 1.5 V to measure the charge capacity (mAh / g), discharge capacity (mAh / g), and initial efficiency (%).
[0403] [Equation 5]
[0404] Initial efficiency (%) = discharge capacity / charge capacity × 100
[0405] In addition, after the button cells prepared in the examples and comparative examples were charged and discharged once in the same manner as above, they were charged at a constant current of 0.1 C until the voltage reached 0.005 V, charged at a constant voltage until the current reached 0.005 C, and charged at a constant current until the voltage reached 0.005 V. Then, they were discharged at a constant current of 0.2 C until the voltage reached 1.5 V to measure the cycle characteristics (capacity retention rate after 50 cycles and 100 cycles, %).
[0406] [Equation 6]
[0407] Capacity retention after 50 cycles (%) = 51st discharge capacity / 2nd discharge capacity × 100
[0408] [Equation 7]
[0409] Capacity retention after 100 cycles (%) = 101st discharge capacity / 2nd discharge capacity × 100
[0410] The content of each element and physical properties of the silicon-based raw material powders, silicon composite materials, and silicon-carbon composite materials of Examples and Comparative Examples are summarized in the following Tables 1 to 4. The characteristics of lithium secondary batteries using the same are summarized in the following Tables 3 and 4.
[0411] [Table 1]
[0412]
[0413] [Table 2]
[0414]
[0415] [Table 3]
[0416]
[0417]
[0418] [Table 4]
[0419]
[0420]
[0421] As can be seen from Table 3 and Table 4 above, in the silicon-carbon composite materials of Examples 1 to 9 of the present invention, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms satisfies a specific range. Therefore, compared with the lithium secondary batteries of Comparative Examples 1 to 4, the performance of the lithium secondary batteries manufactured using the same in terms of discharge capacity, initial efficiency and capacity retention rate is significantly improved.
[0422] Specifically, the lithium secondary batteries of Examples 1 to 7 using silicon-carbon composite materials with a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.03 to 0.44 have a discharge capacity of 1621 mAh / g to 1923 mAh / g, an initial efficiency of 83.6% to 92.5% and a capacity retention rate of 85% or higher in most cases, indicating that the performance of the lithium secondary batteries is excellent as a whole.
[0423] At the same time, when comparing the lithium secondary battery of Comparative Example 1 (the only difference is that the etching in the process of Example 1 is not performed), the secondary battery of Example 1 has a discharge capacity of 1849mAh / g, an initial efficiency of 84.8% and a capacity retention rate of 85.3%, while the lithium secondary battery of Comparative Example 1 has a discharge capacity of 1542mAh / g and an initial efficiency of 74.8%, indicating that the discharge capacity and initial efficiency of Comparative Example 1 are significantly reduced compared with the previous Example 1. This is understood to be because in the lithium secondary battery of Comparative Example 1, etching is not performed in the preparation of the silicon-carbon composite material, thereby leaving excess SiO2 (an irreversible substance).
[0424] In addition, when comparing the secondary battery of Example 1 in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is 0.44 and the secondary batteries of Comparative Examples 2 to 4 in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is 0.48 to 0.76, the secondary battery of Example 1 has an initial efficiency of 84.8% and a capacity retention rate of 85.3%, while the lithium secondary batteries of Comparative Examples 2 to 4 have an initial efficiency of 79.8% or less and a capacity retention rate of 78% or less, indicating that the performance is significantly reduced compared with the lithium secondary battery of Example 1. In addition, the lithium secondary battery of Comparative Example 4 has a discharge capacity of 1553 mAh / g, which is significantly reduced compared with the lithium secondary batteries of the embodiments.
[0425] In particular, in the silicon-carbon composite materials of comparative examples 2 to 4, a large number of pores exist in the composite materials even after the carbon layer is formed, which increases the BET of the composite materials and causes some side reactions with the electrolyte, resulting in a decrease in the capacity retention rate of the lithium secondary battery compared to the lithium secondary battery of the embodiment.
[0426] In addition, when the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) is less than 0.01, the preparation of the silicon-carbon composite material is difficult.
[0427] Meanwhile, in the above Table 4, the silicon-carbon composite materials (2) of Examples 8 and 9 (each including two carbon layers, the carbon layer including a first carbon layer and a second carbon layer) are composite materials in which a second carbon layer is formed on the first carbon layer of the silicon-carbon composite materials of Examples 2 and 4, respectively, by spray drying. Since a double carbon layer is formed, the strength of the outer shell layer is further improved, and the bonding (adhesion) between the silicon-carbon composite material and the binder is enhanced, thereby reducing the electrode expansion rate. Therefore, after 100 cycles, the capacity retention rate of the lithium secondary battery is improved.
[0428] Therefore, the performance of lithium secondary batteries can be uniformly improved by controlling the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material. In addition, the secondary battery characteristics can be controlled by changing the shell structure of the silicon-carbon composite material.
[0429] [Reference Symbols of Drawings]
[0430] 10: Porosity (voids)
[0431] 20: Silicon particles
[0432] 40: Carbon layer (first carbon layer)
[0433] 45: Carbon
[0434] 50: Carbon layer (second carbon layer)
[0435] (1) Chemical thermal decomposition deposition method
[0436] (2) Liquid coating method
Claims
1. A silicon-carbon composite material, comprising silicon particles and carbon, wherein: The molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite material is 0.01 to 0.
45.
2. The silicon-carbon composite material according to claim 1, wherein: The silicon-carbon composite material has a core-shell structure, the core contains silicon particles and carbon, and the shell includes a carbon layer.
3. The silicon-carbon composite material according to claim 1, wherein: The silicon-carbon composite material includes pores therein, and a porosity of the silicon-carbon composite material is 10% or less.
4. The silicon-carbon composite material according to claim 2, wherein: The shell includes a first carbon layer including at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene, reduced graphene oxide, and carbon nanotube.
5. The silicon-carbon composite material according to claim 2, wherein: The shell includes two or more carbon layers, the carbon layers including a first carbon layer and a second carbon layer, The first carbon layer includes at least one selected from amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor graphene and carbon nanotube, and The second carbon layer includes reduced graphene oxide.
6. The silicon-carbon composite material according to claim 1, wherein: Based on the total weight of the silicon-carbon composite material, the content of oxygen (O) in the silicon-carbon composite material is 0.5 wt % to 10 wt %, the content of silicon (Si) is 38 wt % to 80 wt %, and the content of carbon (C) is 18 wt % to 60 wt %.
7. The silicon-carbon composite material according to claim 2, wherein: The content of carbon (C) inside the inner core of the silicon-carbon composite material is 16 wt % to 45 wt % based on the total weight of the silicon-carbon composite material.
8. The silicon-carbon composite material according to claim 5, wherein: The content of oxygen (O) in the reduced graphene oxide in the second carbon layer is 0.5 wt % to 10 wt % based on the total weight of the reduced graphene oxide.
9. The silicon-carbon composite material according to claim 5, wherein: In the Raman spectrum obtained by Raman spectroscopy of the silicon-carbon composite material, when the -1 Up to 2760cm -1 The intensity of the 2D band peak that appears in the range of 1500 cm is I2D. -1 Up to 1660cm -1 The intensity of the G band peak that appears in the range of IG is 1280cm -1 Up to 1400cm -1 When the intensity of the D band peak appearing in the range is ID, the following relationship 4 is satisfied: [Equation 4] 0.5<(I2D+IG) / ID≤2.
0.
10. The silicon-carbon composite material according to claim 1, wherein: The silicon-carbon composite material also comprises silicon oxide (SiO x , 0.4≤x≤2).
11. A method for preparing the silicon-carbon composite material according to claim 1, the method comprising: A first step of etching a silicon-based raw material powder using an etching solution containing a compound containing fluorine (F) atoms; filtering and drying the product obtained by etching to prepare a second step of a silicon composite material; as well as The third step is to coat the inside of the silicon composite material with carbon using a chemical thermal decomposition deposition method or to coat the inside of the silicon composite material with carbon and form a carbon layer on the surface thereof to obtain a silicon-carbon composite material.
12. The method for preparing a silicon-carbon composite material according to claim 11, wherein: The third step includes forming carbon in the inner core and forming a first carbon layer in the outer shell by injecting at least one compound selected from the group consisting of the following Formulas 1 to 3 and reacting in a gaseous state at 400° C. to 1200° C.: [Formula 1] C N H (2N+2-A) [OH] A In Formula 1, N is an integer from 1 to 20, A is 0 or 1, [Formula 2] C N H (2N-B) In Formula 2, N is an integer from 2 to 6, B is an integer from 0 to 2, [Formula 3] C x H y O z In Formula 3, x is an integer of 1 to 20, y is an integer of 0 to 25, and z is an integer of 0 to 5. 13 . The method for preparing a silicon-carbon composite material according to claim 12 , further comprising a fourth step of forming a second carbon layer on the first carbon layer using a liquid coating method after forming the first carbon layer. 14 . A negative electrode active material, comprising the silicon-carbon composite material according to claim 1 . 15 . A lithium secondary battery comprising the negative electrode active material according to claim 14 .
Citation Information
Patent Citations
Porous silicon-based negative electrode active material and lithium secondary battery containing the same
JP2016502253A
Anode active material, method of preparing the same, anode and lithium battery containing the material
CN101510607A
Organic light emitting display device having touch structure of in-cell type
KR102170368B1
KR20210055137A
Cited By
Lithium secondary battery, negative electrode active material and preparation method therefor, and electric device
WO2026166257A1
